Contriving emotional resilience through spirituality in the light of Vedanta - Narasimhan, Pavithra Lakshmi; Saputra, Heru (Postgraduate Program of State Islamic University (UIN) Salatiga Jl. Lingkar Salatiga Km. 02 Salatiga, Indonesia https://pps.uinsalatiga.ac.id/, 2023)
This study examines the Indian perspective on emotions, focusing on the concept of Gunas or Subjective Experiences. Indian Philosophies emphasize the transient nature of emotions and advocate for achieving emotional equilibrium through allegiance to a higher power and surrender. The study concludes that spirituality plays a crucial role in shaping individuals' emotional experiences, contributing to improved mental well-being and reduced narcissistic tendencies. Religious practices foster a sense of security and trust in a